2010
DOI: 10.1002/eji.201040416
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of ICOS/ICOS ligand costimulation in NOD mice results in autoimmune deviation toward the neuromuscular system

Abstract: NOD mice spontaneously develop insulin-dependent diabetes around 10-40 wk of age. Numerous immune gene variants contribute to the autoimmune process. However, genes that direct the autoimmune response toward b cells remain ill defined. In this study, we provide evidence that the Icos and Icosl genes contribute to the diabetes process. Protection from diabetes in ICOS À/À and ICOSL À/À NOD mice was unexpectedly associated with the development of an autoimmune disorder of the neuro-muscular system, characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 44 publications
4
53
1
2
Order By: Relevance
“…4A). ICOS, a T cell costimulatory molecule upregulated on activated T cells, has also been implicated in the regulatory function of Tregs (24,34,35). Administration of blocking Ab to ICOS completely abrogated protection by CD4 + 24abNOD type II NKT cells (Fig.…”
Section: Icos/icos-l Interaction Was Necessary For Type II Nkt Cell Rmentioning
confidence: 93%
See 1 more Smart Citation
“…4A). ICOS, a T cell costimulatory molecule upregulated on activated T cells, has also been implicated in the regulatory function of Tregs (24,34,35). Administration of blocking Ab to ICOS completely abrogated protection by CD4 + 24abNOD type II NKT cells (Fig.…”
Section: Icos/icos-l Interaction Was Necessary For Type II Nkt Cell Rmentioning
confidence: 93%
“…The 24abNOD mice (8), BDC2.5 TCR transgenic NOD mice (BDC2.5 NOD mice) (18), and NOD.scid mice were bred at the Experimental Biomedicine Animal Facility at the University of Gothenburg. BDC2.5 NOD mice deficient for ICOS and their littermate controls (24) and Ca 2/2 BDC2.5NOD (25) were bred at Hôpital Cochin/St. Vincent de Paul (Paris, France).…”
Section: Micementioning
confidence: 99%
“…In contrast to T1D-resistant ICOS 2/2 NOD mice, ICOS blockade in BDC2.5 mice and NOD neonates or ICOS deficiency in BDC2.5 mice exacerbated T1D. However, in the reported studies, the expression or function of ICOS was solely examined on CD25-expressing (CD25 + CD69 2 T cells), not purified Foxp3 + , Tregs enriched from inflamed pancreatic sites (21)(22)(23). Notably, IL-2 therapy augments Treg numbers in the pancreas and induces the expression of various Treg-associated proteins such as Foxp3, CD25, Bcl-2, and ICOS (24).…”
mentioning
confidence: 99%
“…These results suggest that impaired generation of Tregs in the thymus of B6.Sle1.ICOS-KO mice is not the cause of their reduced frequency in the secondary lymphoid tissue. Although it was suggested that ICOS has a differentiation and regulatory function (59)(60)(61), no study has examined the role of ICOS on Tregs in lupus. Further research is necessary to understand the properties of Tregs in the context of the ICOS-sufficient and ICOS-deficient B6.Sle1 lupus-prone models.…”
Section: Cd8mentioning
confidence: 99%